The Linguistic Difference Between English and Russian - Tall, Ousseynou (Advances in Social Sciences Research Journal, 2022)
This article is a comparative analysis of two international languages, Russian and French. It focuses on the differences and similarities between the two languages. Since Russian and French are originally very different languages, it’s extremely important to sort out the identical aspects and differentiate them from the non-identical aspects. Apart from the difference in origins, the two languages are as well very different in terms of phonetics, grammar, lexicology or word building.